Leadership and Teacher Engagement in Collaborative Curriculum Implementation: Evidence from Indonesia - Yoyon Indra Joni; Asti Putri Kartiwi; Manap Somantri (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
Implementing the Merdeka Curriculum in Indonesia requires a strong collaborative culture among educational stakeholders to ensure effective learning outcomes. This study aims to analyse how leadership and teacher engagement shape collaborative curriculum implementation in senior high schools. Using a qualitative design with an interpretive approach, data were obtained from interviews with principals, vice-principals, teachers, and students, supported by observation and document analysis. Thematic analysis was applied to interpret the data. The findings indicate that collaborative leadership fosters curriculum effectiveness through open communication, shared responsibility, participatory decision-making, and collective problem-solving. Teacher engagement plays a pivotal role in strengthening collaboration and maintaining consistency in curriculum execution. Nonetheless, challenges such as differing perceptions, workload imbalance, and limited time allocation hinder optimal collaboration. The study concludes that leadership collaboration and teacher engagement are critical drivers of successful curriculum implementation. Theoretically, this research contributes to the understanding of collaborative leadership in educational reform, while practically, it provides insights for school leaders to develop sustainable professional collaboration frameworks within the Merdeka Curriculum.